A numerical investigation of the effects of ice accretion on the aerodynamic and structural behavior of offshore wind turbine blade. Issue 6 (December 2021) - Lagdani, Oumnia; Tarfaoui, Mostapha; Nachtane, Mourad; Trihi, Mourad; Laaouidi, Houda
In recent years, several wind turbines have been installed in cold climate sites and are menaced by the icing phenomenon. This article focuses on two parts: the study of the aerodynamic and structural performances of wind turbines subject to atmospheric icing. Firstly, the aerodynamic analysis of NACA 4412 airfoil was obtained using QBlade software for a clean and iced profile. Finite element method (FEM) was employed using ABAQUS software to simulate the structural behavior of a wind turbine blade with 100 mm ice thickness. A comparative study of two composite materials and two blade positions were considered in this section. Hashin criterion was chosen to identify the failure modes and determine the most sensitive areas of the structure. It has been found that the aerodynamic and structural performance of the turbine were degraded when ice accumulated on the leading edge of the blade and changed the shape of its profile.